KAJIAN NUTRISI CRACKERS TEPUNG GAYAM (Study of Nutrition of Crackers Gayam) (Jurnal Teknologi Pangan, 2015)
Abstract Crackers is a food products made from flour, fat, sugar and salt are fermented by yeast, then baked in layers created with temperature 175C, and continued with a temperature of 250C (Manley, 1983). The Leguminose family gayam seeds contain lots of carbohydrates, fiber, and protein, used as a replacement for part of the flour (Epriliati, 2002). Baking powder (NaHCO3) is added as a developer that would reduce violence on crackers due to high fiber. This research aims to make crackers by specifying substitution substitution is the best among the flour on wheat flour gayam, with the addition of baking powder (NaHCO3) to produce crackers as a functional food that is high in fiber and protein. The research method used a factorial completely randomized design which is composed of two factors, namely the first factor is the substitution of flour on wheat flour gayam (10; 20; 30%) and second factor is the addition of baking powder (NaHCO3) (0,3; 0,5; and 0.7%) with three replicates. The results showed that the best treatment on substitution treatment gayam (20%) flour on wheat flour (80%), with the addition of baking powder (NaHCO3) 0.5% (P2Y2). The treatment has a moisture content of 2,179%; 13,936% protein; 2,422 fiber content%; ash content% 1,564; and texture (crispness) 0,116 mm/sec gr, and based on the assessment of organoleptik gives the level of fondness towards fondness sense 5,29 (really like); 4,65 texture (like); and the sight of 4.71 out (like).   Keyword : Crackers, gayam flour, baking powder,   Abstrak Crackers merupakan produk pangan yang dibuat dari tepung terigu, lemak, gula dan garam yang difermentasi oleh yeast, dibuat berlapis-lapis kemudian dipanggang dengan suhu 1750C, dan dilanjutkan dengan suhu 2500C (Manley, 1983). Biji gayam famili Leguminose yang banyak mengandung karbohidrat, serat, dan protein, digunakan sebagai pengganti sebagian tepung terigu (Epriliati, 2002). Baking powder (NaHCO3) yang ditambahkan sebagai bahan pengembang yang akan mengurangi kekerasan pada crackers akibat tingginya serat. Penelitian ini bertujuan untuk membuat subtitusi crackers dengan menentukan subtitusi terbaik antara tepung gayam pada tepung terigu dengan penambahan baking powder (NaHCO3) untuk menghasilkan crackers sebagai satu makanan fungsional yang tinggi serat dan protein.Metode penelitian yang digunakan adalah RAL yang tersusun atas 2 faktor yaitu faktor I adalah subtitusi tepung gayam pada tepung terigu (10; 20; dan 30%) dan faktor II adalah penambahan baking powder (NaHCO3) (0,3; 0,5; dan 0,7%) dengan 3 kali ulangan. Hasil penelitian menunjukkan bahwa perlakuan terbaik pada perlakuan subtitusi tepung gayam (20%) pada tepung terigu (80%), dengan penambahan baking powder (NaHCO3) 0,5% (P2Y2). Perlakuan tersebut mempunyai kadar air 2,179%; kadar protein 13,936%; kadar serat 2,422%; kadar abu 1,564%; dan tekstur (kerenyahan) 0,116 mm/gr dtk, dan berdasarkan penilaian organoleptik memberikan tingkat kesukaan terhadap kesukaan rasa 5,29 (sangat suka); tekstur 4,65 (suka); dan kenampakan 4,71 (suka).   Kata kunci : cracker, tepung gayam, pengembang